Religio Politics of Puri and Balinese Community Development - Marijan, Kacung; Wirawan, Ida Bagus; Pinatih, I Gusti Ayu Agung Dewi Sucitawathi (Political Science Program, Universitas Negeri Semarang, 2022)
Balinese history records the existence of the puri as a center of power through a monarchy system led by a king (puri) from the early 10th century to the early 20th century. Puri in Bali also plays a role in various religious ceremonial rituals and traditional activities. The religious ideology of the puridoes not only play a role in the realm of religion, but has expanded into the cultural, social, economic and political realms. This study attempts to describe the relationship between the political religious of the puri and the community development program. The theory used to analyze is World Desecularization Theory and Patron-Client Theory. The research method used is a qualitative approach which is located in Gianyar Regency and is supported by data originating from books and journals. The results of the study found that the religious ideology of the puri had a positive relationship with the development progress of the community. Not infrequently regional development programs originate from these religious ideas. This research also explains the concept of puri political religios, in which religion in this case not only works to build an ideological ties, but more importantly religion is able to build social and economic ties for a society. This model of political religion indirectly maintains the political power of the puri in Bali.